2005
DOI: 10.1016/j.ejpain.2004.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Opioid switch in palliative care, opioid choice by clinical need and opioid availability

Abstract: Availability of different WHO-step 3 opioids has encouraged the discussion on their value and led to the concepts of opioid rotation. Rotation is suggested, when other measures fail to achieve optimal analgesia and tolerability in cancer pain treatment. Opioid use was assessed in a prospective cohort study of 412 palliative care patients from 14 inpatient and outpatient palliative care facilities in Germany. The most frequently used opioids at baseline were morphine and fentanyl. The most frequent changes in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The true opioid switching rate was about 12% and was higher in the inpatient setting. 17 Interestingly, change to the parenteral route accounted for a further 30% of opioid substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…The true opioid switching rate was about 12% and was higher in the inpatient setting. 17 Interestingly, change to the parenteral route accounted for a further 30% of opioid substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies the patient population was unclearly described. Moreover, only five studies gave some indication that advanced cancer patients were included in the study [1923]. Unfortunately, these studies reported only over a short period of follow-up (7–28 days) and clear information on previous opioid use was lacking (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies indicate that in 21 to 44% of the patients, opioid rotation is used 52–56 . In prospective studies, those percentages are 12 57 and 25% 58 . There are no randomized controlled trials investigating the efficacy of opioid rotation.…”
Section: Evidence On Opioid Rotationmentioning
confidence: 99%
“…Since then, more information has become available. Published studies are often based on retrospective chart reviews, but prospective studies have also been conducted 52,57 . Almost all trials demonstrated that opioid rotation results in a better pain relief and/or less side effects.…”
Section: Evidence On Opioid Rotationmentioning
confidence: 99%